FRICTIONAL AND TACTILE COMPRESSION OF SOME POLYMERIC FABRICS (Sciences & Technology. A, exactes sciences, 2000)
One of the first concerns of this study was the meaningful way in which friction could be characterized in fibrous polymers which behave differently from materials in which classical law apply.The frictional behavior of some polymeric fabrics was analyzed using a structural model and experimental method which provided reproducible results of frictional values. The friction parameters used in this study were the average coefficient of friction µ, and the friction indices a and n. The structural model applied is based on the estimation of the true area of contact from the generalized pressure-area curve of the asperities when tests were performed on samples of various types of structures.